Short-term combined training reduces hepatic steatosis and improves hepatic insulin signaling - Pereira, Rodrigo Martins (2021)
Hepatic steatosis is directly associated with hepatic inflammation and insulin resistance, which is correlated with hyperglycemia and type 2 diabetes mellitus (T2DM). Aerobic and strength training have been pointed out as efficient strategies against hepatic steatosis. However, little is known about the effects of the combination of those two protocols on hepatic steatosis. Therefore, this study aimed to evaluate the impact of short-term combined training (STCT) on glucose homeostasis and in the synthesis and oxidation of fat in the liver of obesity-induced mice with hepatic steatosis. Swiss mice were distributed into three groups: control lean (CTL), sedentary obese (OB), and combined training obese (CTO). The CTO group performed the STCT protocol, which consisted of strength and aerobic exercises in the same session. The protocol lasted seven days. The CTO group reduced the glucose levels and fatty liver when compared to the OB group. Interestingly, these results were observed even without reductions in body adiposity. CTO group also showed increased hepatic insulin sensitivity, with lower hepatic glucose production (HGP). STCT reduced the expression of the lipogenic genes Fasn and Scd1 and hepatic inflammation, as well as increased the ACC phosphorylation and the oxidative genes Cpt1a and Ppara, reverting the complications caused by obesity. Since this protocol increased lipid oxidation and reduced hepatic lipogenesis, regardless of body fat mass decrease, it can be considered an effective non-pharmacological strategy for the treatment of hepatic steatosis.